2014
DOI: 10.1007/s00198-014-3000-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of alendronate and vitamin D in patients with normocalcemic primary hyperparathyroidism

Abstract: The results of this study indicate that alendronate/cholecalciferol increases BMD in postmenopausal women with NPHPT. Alendronate/cholecalciferol or vitamin D alone does not affect serum or urinary calcium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
31
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(36 citation statements)
references
References 45 publications
2
31
0
3
Order By: Relevance
“…There are little data available about the impact of medical therapy on patients with normocalcaemic disease. Alendronate improved BMD in a small cohort 151 .…”
Section: Managementmentioning
confidence: 88%
“…There are little data available about the impact of medical therapy on patients with normocalcaemic disease. Alendronate improved BMD in a small cohort 151 .…”
Section: Managementmentioning
confidence: 88%
“…However, nearly 27-33% of asymptomatic patients are at a high risk of disease progression, hypercalcemia, and other related symptoms (30,31). Furthermore, on the spectrum of asymptomatic PHPT patients, those with normocalcemic PHPT can develop kidney and bone involvement (32). Therefore, a parathyroidectomy is also considered appropriate for patients with asymptomatic PHPT (24).…”
Section: Discussionmentioning
confidence: 99%
“…Among the few studies evaluating therapies, Koumakis and colleagues reported improved bone mineral density at 1 year after parathyroidectomy in both normocalcaemic and hypercalcaemic groups in a longitudinal cohort. In a small prospective open‐label randomized trial, medical treatment using alendronate and cholecalciferol seemed to improve the bone mineral density in postmenopausal women.…”
Section: Discussionmentioning
confidence: 99%